And now the end is near: enlivening and politizising the geographies of dying, death and mourning. (17th February 2016) - Stevenson, Olivia; Kenten, Charlotte; Maddrell, Avril
Abstract : A new body of scholarship on death and loss has emerged as a sub-field within social and cultural geography. This work has done much to draw geographers' attention to questions of death, dying and remembrance and likewise to bring a spatial perspective to interdisciplinary death studies. Whilst deathscapes have been framed within geographical work as incorporating material, embodied and virtual spaces, to date Anglo-American and European studies have tended to focus on the literal and representational spaces of the end of life, sites of bodily remains and memorialization. With a number of important exceptions, embodied and dynamic experiences of dying, death and survival have been absent within the geographies of death. This special section aims to broaden the scope, and to resist simple dichotomies of life and death, and to be especially attentive to the embodied and visceral experiences, practices and processes of dying, death and survival. In this introduction, we explore themes of dying/s, death/s and survival/s across varied international, national and cultural contexts, as discussed in the contributing papers and raised by the politics of recent events. This collection offers an expanded and enlivened approach to research, documenting facing death/s, journeys at the end of life, living through, on and with life-limiting illnesses, living with loss and the interconnected spatialities that these experiences and practices evoke for individuals and wider social groups. They open up new spaces of P/politics and emotions, challenging limited political and medicalized frames. The papers also raise methodological questions and present a challenging agenda for future research. This special section grew out of sessions we organized for the 2012 RGS-IBG Annual International Conference at the University of Edinburgh.